Longterm follow‐up of small pancreatic cystic lesions in liver transplant recipients. Issue 3 (8th February 2017) - Vidhyarkorn, Sirachat; Siripongsakun, Surachate; Yu, Jennifer; Sayre, James; Agopian, Vatche G.; Durazo, Francisco; Lu, David S.
Abstract : Incidental small pancreatic cystic lesions (PCLs) are often found on preoperative imaging in patients undergoing orthotopic liver transplantation (OLT). Although these are considered benign or of low malignant potential, the influence of immunosuppression after OLT may be of concern. The aim of this study was to observe the longterm outcome of these small PCLs in post‐OLT patients. An institutional OLT database of 1778 consecutive OLT patients from January 2000 to December 2010 was analyzed. Computed tomography, magnetic resonance imaging, or endoscopic ultrasound at the time of OLT and all subsequent imaging, cytology, fluid analysis of PCLs, and patient status were evaluated. A total of 70 patients with 182 PCLs, of benign or low malignant potential, were identified with a mean follow‐up time of 64 months. At initial diagnosis of PCLs in 48 patients, 7 branch duct–type intraductal papillary mucinous neoplasms (B‐IPMNs), 1 serous cystadenoma (SCA), and 40 nonspecific benign cysts were identified. Final diagnosis at the end of the follow‐up revealed 16 B‐IPMNs, 3 SCAs, and a mixed acinar‐neuroendocrine carcinoma, in which the latter developed 9 years after initial diagnosis of B‐IPMN. During the follow‐up time, average increase in size and number of PCLs were 4.5 mm and 1.4, respectively ( P  < 0.001 for both). The majority of incidental PCLs in OLT patients showed an indolent behavior despite immunosuppression. Risk of malignancy development was very low and comparable with normal population. Liver Transplantation 23 324–329 2017 AASLD .